The Analysis Of Deterioration Of Village Road: A Case Of Palasah-Majalengka - Kharisma, Galuh; Rifai, Andri Irfan; Taufik, Mohamad; Prasetijo, Joewono (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
They are raising international issues related to road maintenance and repair. Road damage occurring in various countries, including cracks, potholes, and surface deformation, significantly impacts transportation safety and efficiency. Many roads in certain regions experience damage, such as cracks, potholes, and surface deformation due to increased traffic loads and extreme weather conditions. This paper aims to analyze road damage in Karamat Village according to Bina Marga standards to identify and understand the causes and effects of such damage. Primary data is collected from field observations at the study site, referred to as primary or first-hand data. The road damage found on Pajaten Road in Karamat Village, Majalengka Regency, includes patches, cracks, disintegration, potholes, and waves. Routine maintenance aims to improve the surface layer quality without increasing structural strength. The Pajaten road section in Karamat Village, Majalengka Regency, has conditions of loose stones, cracks, patches, potholes, and waves. The Directorate General of Highways states that the calculation results have a priority order 10, placing it in the priority group > 7. According to Bina Marga, road damage is addressed through a routine maintenance schedule. Patching is recommended and suggested for repairing road cracks, ruts, and collapses.